Pengaruh SBIS Dan PUAS Terhadap Tingkat Inflasi Melalui Operasi Moneter Syariah Pada Periode 2011-2015 - Marisa Ayu Andarini; Tika Widiastuti (Universitas Airlangga, 2016)
This study aims to determine the relationship directly or indirectly between SBIS and PUAS into inflation by Sharia Monetary Operations. The approach used is a quantitative approach using path analysis technique with four variables are SBIS and PUAS as exogenous variable, the inflation rate as an endogenous variable and OMs as an intervening variable.The results show that SBIS and PUAS have a positive direct correlation to inflation. This show that the SBIS and PUAS still did’t able to meet expectations in order to reduce the rate of inflation. In this study may also indicate that the SBIS relate indirectly to inflation through OMs. OMs be able to suppress compared to inflation growth rate of SBIS and PUAS variable, PUAS doesnt have a relation to inflation through OMs. Therefore, from this study is expected the government to reassess the effectiveness of Islamic monetary transmission in suppressing the inflation growth rate.